Notes from the metalevel: Introduction to algorithmic music composition - Taube, Heinrich K. (London Taylor & Francis, 2004)
This is a first-class book for anyone interested in using the computer for music composition. Be forewarned though, it is not a guide to GarageBand or any other MIDI sequencer or hard-disk recorder. The author uses his own Common Music progamming language as the basis for an exploration into techniques and methods of making music that would be most unlikely without the assistance of the computer. Btw, the Common Music software is included with the book, in packages for Windows, Linux, and the Mac, so you can work with the book's examples immediately.The text is clear and easy to understand, reflecting the author's experience as an educator. The examples are helpful and open-ended, lending themselves to further explorations. In addition to the regular examples the book includes a number of more extended projects based on work by composers such as Steve Reich and Gyorgy Ligeti.No previous experience with a music progamming language is necessary, but if you have a background in Lisp or another object-oriented language you'll feel right at home with this book's Lisp-based example code. If you know nothing about programming the book's first chapters will bring you quickly up to speed on the basics needed to work with the rest of it.